Evaluasi Implementasi Usaha DapureSA Berbasis Analisis SWOT - Sira Albina; Sabinus Beni; Yeremia Niaga Atlantika; Usman Usman (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to find out the strategies that can be applied to DapureSA's business located in Setia Budi Village, Bengkayang District. This study uses SWOT analysis to find out the strengths, weaknesses, opportunities, and existing threats. This research uses a descriptive method with a qualitative approach where primary data is obtained directly from consumers while secondary data is obtained through books, magazines, journals and articles. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the study show that the DapureSA business is quite popular with consumers who say that the products from the DapureSA business taste good at a low price, the quality offered is very good. In conclusion, DapureSA's business can experience an increase in turnover if it continues to develop products and continue to innovate by adding various flavor variants, increasing production volumes, maintaining price stability, maintaining production quality and finding strategic places to open outlets